Temporal Variation in the Microbiome of Acropora Coral Species Does Not Reflect Seasonality - Epstein, Hannah E.; Smith, Hillary A.; Cantin, Neal E.; Mocellin, Veronique J. L.; Torda, Gergely; van Oppen, Madeleine J. H. (Frontiers in Microbiology, 2019)
The coral microbiome is known to fluctuate in response to environmental variation and has been suggested to vary seasonally. However, most studies to date, particularly studies on bacterial communities, have examined temporal variation over a time frame of less than one year, which is insufficient to establish if microbiome variations are indeed seasonal in nature. The present study focused on expanding our understanding of long-term variability in microbial community composition using two common branching coral species, Acropora hyacinthus and Acropora spathulata, at two mid-shelf reefs on the Great Barrier Reef. By sampling over a two-year time period, this study aimed to determine whether temporal variations reflect seasonal cycles. Community composition of both bacteria and Symbiodiniaceae was characterized through 16S rRNA gene and ITS2 rDNA metabarcoding. We observed significant variations in community composition of both bacteria and Symbiodiniaceae among time points for A. hyacinthus and A. spathulata. However, there was no evidence to suggest that temporal variations were cyclical in nature and represented seasonal variation. Clear evidence for differences in the microbial communities found between reefs suggests that reef location and coral species play a larger role than season in driving microbial community composition in corals. In order to identify the basis of temporal patterns in coral microbial community composition, future studies should employ longer time series of sampling at sufficient temporal resolution to identify the environmental correlates of microbiome variation.